2021
DOI: 10.3390/biom11050720
|View full text |Cite
|
Sign up to set email alerts
|

Shorter Chain Triglycerides Are Negatively Associated with Symptom Improvement in Schizophrenia

Abstract: Schizophrenia is a serious mental disorder requiring lifelong treatment. While medications are available that are effective in treating some patients, individual treatment responses can vary, with some patients exhibiting resistance to one or multiple drugs. Currently, little is known about the causes of the difference in treatment response observed among individuals with schizophrenia, and satisfactory markers of poor response are not available for clinical practice. Here, we studied the changes in the levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Blood collection, lipid extraction, chromatography, and mass spectrometry measurements, lipid data processing, and compound annotation were conducted as in Tkachev et al, with small modifications (eMethods and eAppendix in Supplement 1). Lipidome measurements were conducted in 4 temporally separate experimental runs, corresponding to the 4 cohorts (CN, DE-AT, RU, and fepRU).…”
Section: Methodsmentioning
confidence: 99%
“…Blood collection, lipid extraction, chromatography, and mass spectrometry measurements, lipid data processing, and compound annotation were conducted as in Tkachev et al, with small modifications (eMethods and eAppendix in Supplement 1). Lipidome measurements were conducted in 4 temporally separate experimental runs, corresponding to the 4 cohorts (CN, DE-AT, RU, and fepRU).…”
Section: Methodsmentioning
confidence: 99%
“…In some studies, changes in lipid levels in SCZ patients have been associated with Positive and Negative Syndrome Scale (PANSS) scores. For example, such correlations have been detected for shorter-chain TGs [41] and oxysterols [55]. Nandeesha (2023) [52] showed that total cholesterol (TC) and TG levels were negatively correlated with cognitive scores.…”
Section: Lipids and Their Role In Neuropsychiatric Disordersmentioning
confidence: 97%
“…Nine studies evaluated the broad panels of different lipid markers in patients with SCZ [31,34,[40][41][42][43][44][45][46] and detected statistical differences in the following lipid classes: fatty acyls, sterols, glycerolipids, sphingolipids, glycerophospholipids, and products of lipid metabolism. Several studies included information about lipids associated with the membranes of erythrocytes [31,47,48].…”
Section: Lipids and Their Role In Neuropsychiatric Disordersmentioning
confidence: 99%
“…The most commonly associated lipid class with antipsychotic treatment was phosphatidylcholines (five studies). Three studies included analyses of metabolites associated with antipsychotic response [9,17,42]. A summary of the untargeted lipidomic studies is in Table 3 and Supplementary Table S3.…”
Section: Untargeted Lipidomic Studiesmentioning
confidence: 99%